PENGUKURAN FAKTOR KOMPENSASI DETEKTOR RENTANG DAYA KNK 50 UNTUK TERAS RSG-GAS - A. Mariatmo; Ir. Edison Edison; Heri Prijanto (Reaktor : Buletin Pengelolaan Reaktor Nuklir, 2016)
PENGUKURAN FAKTOR KOMPENSASI DETEKTOR RENTANG DAYA KNK 50 UNTUK TERAS RSG-GAS. Telah dilakukan pengukuran faktor kompensasi detektor neutron rentang daya KNK 50 yang dipasang disekitar teras RSG-GAS. Pengukuran ini diperlukan untuk memeriksa kinerja bagian kompensasi dari detektor  setelah beroperasi selama lebih dari satu tahun.  Ketika reaktor sedang beroperasi, teras reaktor tidak hanya memancarkan neutron tetapi juga sinar gamma yang  akan menyumbang pada sinyal arus detektor. Faktor kompensasi ini menunjukkan kemampuan detektor untuk menetralkan pengaruh sinar gamma sehingga sebagaimana desainnya detektor ini seharusnya hanya mengukur neutron saja. Pengukuran ini dilakukan pada dua buah detektor rentang daya KNK 50 terpasang  setelah sehari reaktor shut down. Elektrode positif kamar sensitif neutron dan gamma diberi tegangan positif yang tetap, sedangkan elektrode negatif kamar kompensasi diberi tegangan negatif yang bervariasi. Untuk setiap variasi tegangan negatif,  arus yang dihasilkan pada elektrode sinyal diukur dan dicatat. Akhirnya diperoleh arus minimum  yang dihasilkan. Faktor kompensasi detektor adalah  prosentase arus minimum ini  terhadap arus mula-mula ketika tegangan negatif nol. Dari hasil pengukuran yang dilakukan, detector JKT03 CX831 memiliki faktor kompensasi 0,45% dan detector JKT03 CX841 memiliki faktor kompensasi 0,41%. Kedua hal ini berada dibawah batas spesifikasi 2%[3*] sehingga kemampuan kompensasi gamma kedua detector tersebut dinyatakan masih baik.  ABSTRACTTHE MEASUREMENTS OF COMPENSATION FACTORS OF THE KNK 50 POWER RANGE DETECTORS FOR THE RSG-GAS’S CORE.  It has been implemented the measurement of compensation factors on the KNK 50 power range neutron detectors installed around the RAG-GAS core.  The measurements are needed to check performance of the compensating part of the detectors after they are used for more than a year. While the reactor are in operation, the core produce neutrons and also gamma rays other which will contribute to current signal of the detectors. The compensation facto rindicate capability of the detectors to neutralize of effect of gamma radiations affect so as its design, that it only measures neutrons. The measurements were performed on two installed KNK 50 power range detector one day after reactor shutdown. The constant positive voltage is applied to the positive electrodes of the neutron and gamma sensitive chambers. While varied negative voltages were applied to the negative electrodes of compensation chamber. For each variation of negative voltage applied, the resulting current at the signal electrode was measured and noted. Eventually, the minimum resulting currents are measured and noted. The compensation factor of the detector is the percentage of the minimum resulting current at the signal electrode to the resulting current when the negative electrode was grounded.  The results of measurements of the detector JKT 03 CX 831 has a compensation factor of 0.45% and a detector JKT03 CX841 has a compensation factor of 0.41%. Both of these detectors is within the specification limits 2%[3*] so that the ability of the gamma compensation detector is functioning properly.